2015
DOI: 10.1080/03949370.2015.1080195
|View full text |Cite
|
Sign up to set email alerts
|

Bird fruit consumption results from the interaction between fruit-handling behaviour and fruit crop size

Abstract: Bird foraging behaviour is a major factor involved in mutualistic interactions of fleshy-fruited plants. Despite much research, we still lack quantified demonstrations of how fruit display traits affect fruit removal behaviour. Although the fruit crop size hypothesis proposes a general mechanism for fruit trait selection, it overlooks the fact that distinctive bird behaviours in a bird assemblage would have different effects on fruit crop size. Here, we show that the relevance of fruit crop size for bird fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
1
27
1
1
Order By: Relevance
“…, Palacio et al . ). Several studies have found that seeds make up the largest proportion in the diet of large Neotropical parrots (Galetti , Matuzak et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Palacio et al . ). Several studies have found that seeds make up the largest proportion in the diet of large Neotropical parrots (Galetti , Matuzak et al .…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that ecological and life history traits explain variation in diet in a trophic generalist group, although with low explanatory power. Differences in body size limit or facilitate the consumption of certain sizes and types of seeds, fruits and flowers, because body size is strongly linked to energetic requirements and abilities in terms of food searching, harvesting and processing (Bowers & Brown 1982, Brown et al 2004, Palacio et al 2017. Several studies have found that seeds make up the largest proportion in the diet of large Neotropical parrots (Galetti 1997, Matuzak et al 2008, Lee et al 2014, Renton et al 2015, whereas flowers, nectar and fleshy fruits make up the largest proportion in small species (Pizo et al 1995, Cotton 2001, Ragusa Netto & Fecchio 2006, Botero-Delgadillo et al 2010, Renton et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As we see it, factors characterizing seed dispersal systems (Snow, 1971;Howe and Estabrook, 1977) that will drive the shape and intensity of selection on fruit crop size fall into three categories: (1) plant traits, such as plant size, fruit size, pulp and nutrient content, and fruiting phenology (Wheelwright, 1993;Burns, 2004Burns, , 2005Sobral et al, 2010;Palacio et al, 2014); (2) bird assemblage traits, related to the functional role of frugivores (Galetti et al, 2013;Morales et al, 2013;Dehling et al, 2016;Palacio et al, 2017b), and (3) environmental or abiotic factors (Hampe, 2003;Márquez et al, 2004;Sobral et al, 2013). We hypothesized that the strength of selection on fruit crop size stems from ecological filtering by constraining certain bird species to interact with a plant population.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit clumps are easily noticeable by birds improving foraging efficiency in terms of decreasing search, travel time and predation risk (Sallabanks ; Ortiz‐Pulido, Albores‐Barajas & Díaz ; Palacio et al . ). In spite of knowing the role played by different plant traits on fruit consumption (Howe & Estabrook ; Alcántara et al .…”
Section: Introductionmentioning
confidence: 97%
“…The number of fruits and their arrangement on the plant enhance conspicuousness, influencing the ability of birds to detect them and their foraging decisions. Fruit clumps are easily noticeable by birds improving foraging efficiency in terms of decreasing search, travel time and predation risk (Sallabanks 1993;Ortiz-Pulido, Albores-Barajas & D ıaz 2007;Palacio et al 2017). In spite of knowing the role played by different plant traits on fruit consumption (Howe & Estabrook 1977;Alc antara et al 1997;Blendinger, Loiselle & Blake 2008;Palacio, Lacoretz & Ordano 2014;Blendinger et al 2015), there is no strong evidence yet on how different combinations of traits affect conspicuousness of fruit display.…”
Section: Introductionmentioning
confidence: 99%